Writing literary worlds in a foreign language proceedings of the Seminar : Helsinki, September 24, 2021 - Garavelli, Enrico 1969-; Rink, Christian; Sanromán Vilas, Begoña (Société Néophilologique, 2022)
"Why do writers decide at some point of their life, more or less freely, to use a language other than their own as a tool for their art? How do they hybridize their own native language using different languages, dialects, dead or artificial languages, in the most varied way, from code mixing to pastiche? And what are the challenges literary multilingualism poses for translators?" To attempt to answer these questions from the point of view of their own particular research field, scholars from all over the world met during a seminar held in Helsinki in the Fall202l. The main aim of the Seminar was to discuss the literary production of non-native speakers/writers. This volume collects the texts of nine of the papers presented on the occasion
Textes en finnois, anglais, allemand, italien
Keywords: Fremdsprache; Mehrsprachigkeit; Literaturproduktion; Littérature / Recherche; Multilinguisme et littérature; Actes de congrès; Konferenzschrift -- Société Néophilologique -- 24.09.2021 -- Helsinki